2019
DOI: 10.1021/acs.jpclett.9b01261
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric “Catastrophe Machines” with Thermally Activated Bistability and Stochastic Resonance

Abstract: The desire to create nanometer-scale switching devices has motivated an active search for bistate macromolecular systems allowing for sharp conformational transitions in response to stimuli. Using full-atomic simulations, we found particular oligomers of thermosensitive polymers, themselves only a few nanometers in size, that possessed conformational bistability and reacted to power loads as nonlinear mechanical systems, termed “catastrophe machines”. We established the bifurcation and hysteresis effects, spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Following Kramer's rate approximation with the collision time for random perturbations ranging from 0.1-10 ps, one can roughly www.videleaf.com estimate the bistability barrier of the oligo-PF-5 spring as 10-15 kBT. Interestingly, the bistability barrier of the oligo-PF-5 spring turned out to be roughly equal to the same value as that for the oligomeric Euler arch described in [42,43]. Even though the reasons for the bistability of the oligo-PF-5 spring and the oligomeric Euler arch were different, the bistability barriers of both bistable oligomeric systems were about ten times larger than the characteristic scale of thermal fluctuations, kBT.…”
Section: Bistable Dynamics Of Oligo-pf-5 Springmentioning
confidence: 70%
See 2 more Smart Citations
“…Following Kramer's rate approximation with the collision time for random perturbations ranging from 0.1-10 ps, one can roughly www.videleaf.com estimate the bistability barrier of the oligo-PF-5 spring as 10-15 kBT. Interestingly, the bistability barrier of the oligo-PF-5 spring turned out to be roughly equal to the same value as that for the oligomeric Euler arch described in [42,43]. Even though the reasons for the bistability of the oligo-PF-5 spring and the oligomeric Euler arch were different, the bistability barriers of both bistable oligomeric systems were about ten times larger than the characteristic scale of thermal fluctuations, kBT.…”
Section: Bistable Dynamics Of Oligo-pf-5 Springmentioning
confidence: 70%
“…Based on these lifetimes and following Kramer's rate approximation with the collision time ranging from 0.1-10 ps, we estimated the bistability barriers of both springs as 10-15 𝑘 𝐵 𝑇. It is noteworthy that the time scales of spontaneous vibrations of the oligo-PF-5 and the oligo-PF-7 springs and their bistability barriers were approximately the same as those of the oligomeric Euler arch described in [42,43]. The bistability barriers of short PF springs appear to be high enough to separate the two states against the thermal noise; on the other hand, the same barriers allowed activation of the transitions between the two states by energetically enriched thermal fluctuations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This article focuses on nanoscale molecular structures whose dynamic prototypes are the textbook bistable mechanical systems known as Euler arches (a beautiful but simple example of a bistable machine which is composed of two rigid rods joined by a hinge with an elastic spring) [27][28][29] and Duffing oscillators [30,31]. In particular, using molecular dynamics simulations, it was found that the long-term conformational dynamics of short rod-shaped thermosensitive oligomers were similar to the bistable dynamics of a Euler arch [29,32,33], while particular oligomers of a helical form stabilized via weak intermolecular interactions could behave as bistable Duffing oscillators [29,34].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent intensive molecular dynamic simulations investigating short oligomeric compounds subjected to force loads have uncovered bistable molecules that exhibit the dynamic behavior resembling that of the Euler arches and Duffing oscillators [ 32 , 33 , 34 ]. These simulations have revealed the presence of mechanic-like bistability in specific oligomeric molecules, accompanied by spontaneous vibrations and stochastic resonance activated by thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%